Primary sclerosing cholangitis - an insidious enemy of the liver - case report - Knop, Kinga; Piasecka, Zuzanna; Kochanowska, Anna; Glaz, Aneta; Wesolek, Ewelina; Kasztelan-Szczerbinska, Beata; Skrzydlo-Radomanska, Barbara (Journal of Education, Health and Sport, 2022)
Background and introduction Primary sclerosing cholangitis (PSC) is a chronic liver disease with features of cholestasis as a result of inflammation and damage to the bile ducts, which can eventually lead to liver fibrosis and parenchymal failure at an advanced stage. Case Report A 22-year-old man was admitted urgently to the Department of Gastroenterology for complaints of abdominal pain, weakness and tarry stools. A panel of detailed examinations was performed to establish the diagnosis. An abdominal ultrasound scan showed significant enlargement of the liver and spleen. Gastroscopy revealed variceal columns of II degree in the lower esophagus, which were cauterized. Laboratory tests confirmed anemia, reduced platelet and white blood cell counts, increased activity of ALT, ASP, GTP, ALP and slight elevation of total bilirubin in the blood. Based on the clinical disease manifestation and the results of diagnostic tests, cirrhosis of unknown origin was suspected. Subsequent magnetic resonance cholangiopancreatography (MRCP) revealed the presence of multiple strictures in the intra- and extrahepatic bile ducts and gave rise to the diagnosis of PSC. Pharmacological treatment was administered. Currently, the patient remains under the close care of the Transplant Clinic, where he undergoes regular checks of liver function, and endoscopic variceal ligation (EVL) as required. Discussion with conclusions The case presented here shows that the course of PSC can be insidious and asymptomatic. Despite the absence of clinical symptoms, the disease can lead to the development of advanced cirrhosis even in patients of young age and be diagnosed as late as at the decompensated stage, when the only treatment option remains organ transplantation.